The Effects of Carrageenan Addition on The Quality of Broiler Chicken Meatballs - Dioq Medi Syahputra; Nazaruddin Nazaruddin; Siska Cicilia (Universitas PGRI Semarang, 2021)
The purpose of this study was to determine the effect of adding carrageenan to the quality of broiler meatballs. The design of this study was a completely randomized design (CRD) with one factor, namely the concentration of carrageenan addition (A). There are 6 treatments, namely 0% (A1), 0.5% (A2), 1% (A3), 1.5% (A4), 2% (A5), and 2.5% (A6) with 3 repetitions. The parameters observed included chemical parameters (moisture content, ash content, protein, fat and fiber) and organoleptic parameters (texture, color, and taste) hedonic. The observed data were analyzed using Analysis of variance at a significant level of 5 %. If there is a significant difference, further tests are carried out using orthogonal polynomials for chemical parameters and Honest Significant Difference (BNJ) at the 5% level for organoleptic parameters. The results showed an increase in the concentration of carrageenan addition caused an elevate in water content, ash content, crude fiber content and protein but a decrease in fat content. Treatment A4 with 1.5% carrageenan is the best formula with a protein content, moisture, ash, fat, crude fiber of 16.94%, 17.12%, 0.85%, 2.38%, 1.65%, respectively and tend to be favored by panelists.